Collaborative Public Management - Robert Agranoff, Michael McGuire (Georgetown University Press, 2004)
Our concern in this book is with the formidable task of dissecting the extent and nature of the process whereby public and nonpublic organizations work together. The era of the manager’s cross-boundary interdependency challenge has arrived, as has the world of working in the network of organizations. Public functions are no longer the exclusive domain of governments. Many seemingly private domains, such as those of business creation, are at the core of public-sector developmental functions. The term ‘‘intergovernmental’’ has new meaning beyond federal–state, state–local, and interlocal connotations, to include quasi-governmental and myriad contractual, regulatory, subventional, reciprocal, and other interactive relationships with organizations outside the public sector. More needs to be known about the core nature of collaborative management, the kinds of collaborative activities that exist, and what can be discovered about the processes of managing collaboration. This study attempts to go beyond the arguments about the importance of interorganizational management by breaking it down into its parts and sequences as well as to make suggestions regarding how to manage the process. As such, the book can be used as a research source by scholars, as well as a supplemental text in many different areas, such as courses in intergovernmental relations, managing networks, urban management, economic development, and general public management. Researching at the boundaries of governments and other organizations, career-long endeavors for the authors, requires a very high level of tolerance for ambiguity. Some say it is a gift and others say it is acquired; we don’t know, but we do know it is not for everyone. Being able to think, talk, and write outside the hierarchy, about transactions between formal entities, may be equivalent to social psychologists looking at interpersonal interactions. The study of boundaries is sometimes avoided because of a lack of concreteness. Clearly, in politics and administration, boundaries are harder to study than those within an organization. But their accelerating prominence means that they cannot be put aside as foci of study.